2012
DOI: 10.7314/apjcp.2012.13.6.2861
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Palliative Prognostic Index to Predict Life Expectancy for Terminally Ill Cancer Patients in a Hospice Consultation Setting in Taiwan

Abstract: Background: The aim of our study was to assess the practical utility of the palliative prognostic index (PPI) as a prognostic tool used by nurse specialists in a hospice consultation setting in Taiwan The sensitivity and specificity for the poor prognosis group was 66% and 71%; the positive predictive value and negative predictive value were 81% and 52%, respectively, to predict patient death within 21 days (area under the curve of the receiver operating characteristic was 0.68). Conclusions: Assessment by PPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 30 publications
(36 reference statements)
2
33
0
2
Order By: Relevance
“…It have been demonstrated life expectancy was involved in the epidemiological profile of cancers (Cheng et al, 2012;). In our current study, apparent rise of the male median onset age of ESCC from 57 to 59, and the female from 57 to 60, respectively, might be attributed to the increase of average life expectancy for Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…It have been demonstrated life expectancy was involved in the epidemiological profile of cancers (Cheng et al, 2012;). In our current study, apparent rise of the male median onset age of ESCC from 57 to 59, and the female from 57 to 60, respectively, might be attributed to the increase of average life expectancy for Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting life expectancy in terminal cancer is important for clinicians because a poor survival estimate can make a clinical decision about appropriate palliative treatment harder [19]. In general, lifespan is difficult to estimate accurately [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…In general, lifespan is difficult to estimate accurately [14,19]. If there are the clinical condition (the common terminal pathway) that include precipitously decreased performance, anorexia-cachexia, dyspnea, dysphagia, and delirium, the signs should preclude the administration of general anesthesia [7,14,19].…”
Section: Discussionmentioning
confidence: 99%
“…Morita et al revealed that the PPI signiicantly reduced overestimation of survival compared to the CPS [39]. In the study of another group, the PPI was assessed by a nurse specialist, and the area under the curve (AUC) of the receiver operating characteristic (ROC) to predict death within 21 days was 0.68 [40]. In Kuwait, Alshemmari et al revealed that the PPI can be a helpful tool in predicting hospital mortality of patients with advanced cancer in an acute care seting and that the hospital mortality rate for patients with a PPI score ≥ 6 was signiicantly higher than for those with a PPI score < 6 (93% versus 56% p < 0.001) [41].…”
Section: Risk Groupsmentioning
confidence: 99%
“…Validation studies of the PPI were performed in Japan, Taiwan, Kuwait, Ireland, the United Kingdom, and Australia [39][40][41][42][43][44][45][46]. Morita et al revealed that the PPI signiicantly reduced overestimation of survival compared to the CPS [39].…”
Section: Risk Groupsmentioning
confidence: 99%